Identifying the gaps between customer expectations and perceptions on service quality dimensions of Islamic banks in Malaysia - Islam, Rafikul; Ahmed , Selim; Abdul Razak, Dzuljastri (Emerald, 2015)
This paper aims to identify the gaps and differences between customer expectations and perceptions on service quality of Islamic banks in Malaysia based on six dimensions of service quality, namely, reliability, responsiveness, assurance, empathy, tangibles and Islamic Shari’ah compliance.